2004
DOI: 10.1111/j.1365-2222.2004.02054.x
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of apoptotic eosinophils but not neutrophils by bronchial epithelial cells

Abstract: Summary Background We have previously demonstrated that human bronchial epithelial cells engulf apoptotic eosinophils. Objectives To compare and contrast the phagocytic capabilities of monocyte‐derived macrophage and primary airway epithelial cells for apoptotic granulocytes. Results Here we compared phagocytosis of human apoptotic eosinophils and neutrophils by small and large airway epithelial cells (SAEC and LAEC) and monocyte‐derived macrophages. Confocal microscopy of F‐actin staining an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 46 publications
2
35
0
2
Order By: Relevance
“…25 CD44 has also been implicated in clearance of apoptotic cells 17 and, as in bacterial phagocytosis, there is evidence that CD44 may function as a coreceptor during this process. For example, ligation of CD44 on macrophages or on airway epithelial cells increases the ensuing uptake of apoptotic neutrophils 19,21 and eosinophils, 20 respectively. During internalization of apoptotic cells there are several potential ligands on the surface of the apoptotic prey that could bind CD44 on the phagocyte plasma membrane, including hyaluronan and CD44 itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 CD44 has also been implicated in clearance of apoptotic cells 17 and, as in bacterial phagocytosis, there is evidence that CD44 may function as a coreceptor during this process. For example, ligation of CD44 on macrophages or on airway epithelial cells increases the ensuing uptake of apoptotic neutrophils 19,21 and eosinophils, 20 respectively. During internalization of apoptotic cells there are several potential ligands on the surface of the apoptotic prey that could bind CD44 on the phagocyte plasma membrane, including hyaluronan and CD44 itself.…”
Section: Discussionmentioning
confidence: 99%
“…16 Observations also point to a role for CD44 in binding, ingestion (phagocytosis), and clearance of apoptotic cells 17 and microbial pathogens. 18 With respect to clearance of apoptotic cells, direct antibody ligation of CD44 on macrophages 19 or on airway epithelial cells 20 enhanced subsequent uptake of apoptotic neutrophils and eosinophils, respectively, suggesting a costimulatory function for the receptor. However, ensuing reports have suggested that some of these effects may be attributed to the Fc portion of the macrophage-bound anti-CD44 antibody interacting with the Fc␥-receptor on the leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The highest expression of P2X7 receptors is on professional phagocytes of monocyte/macrophage lineage including microglia (10), but P2X7 also has ubiquitous distribution, and other cell types (e.g. epithelial and both mature and progenitor neuronal cells) are able to recognize and engulf apoptotic cells at slower rates (11)(12)(13). Apart from certain complement components (14), physiological regulators in the process of non-inflammatory removal of apoptotic cells have yet to be identified.…”
Section: Rapid Phagocytosis Of Non-opsonized Particles Including Apopmentioning
confidence: 99%
“…Several other types of epithelial cells have been shown to be capable of phagocytosis in vitro. Human alveolar and airway epithelial cells can engulf apoptotic eosinophils [21][22][23], suggesting that epithelial-mediated phagocytosis may help to accelerate the resolution of inflammation in the lung.…”
Section: The Role Of Non-professional Phagocytes In Mammary Gland Invmentioning
confidence: 99%